Flexible bronchoscopic excision of a tracheal mass under extracorporeal membrane oxygenation - Kim, Jae Jun (J Thorac Dis, 2015)
Tracheal tumor is a rare but life-threatening condition that can cause obstruction of the airway. Management of tracheal tumors is very challenging and includes surgical resection, radiotherapy, and therapeutic bronchoscopy. Herein, we present a very rare case of an 88-year-old female patient with a tracheal mass due to direct invasion of a mediastinal teratoma. We devised a new method for resection of the tracheal mass because management of her airway and the tracheal mass by conventional methods was impossible. We successfully resected the tracheal mass with flexible bronchoscopic electrocautery under extracorporeal membrane oxygenation (ECMO) without any complications. When management of a patient’s airway and tracheal mass are impossible by conventional methods, this technique may be very useful.